Perbedaan Sikat Gigi Biasa Dengan Sikat Gigi Elektrik Terhadap Penurunan Debris Indeks Pada Murid Kelas V Madrasah Diniyah Islamiyah Kindaung Banjarmasin - Eddy Rahman; M. Bahrul Ilmi (HB PRESS, 2019)
Brushing teeth in a mechanical way is still considered the most effective way, even though the use of toothbrush with the help of special tools such as electric toothbrush. The purpose of this study was to find out there are differences in ordinary toothbrush with electric toothbrush against decreasing index debris in fifth grade students of MDIM Kindaung Banjarmasin. This type of research is a real experiment with the design of